HUMANIZING: A CHARACTER BUILDING - DEWI ASIA; MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
It is a commonly known fact that childrenÃ¢â‚¬â„¢s education always begins with socialization to their culture and community, and only later upon their exposure to other communities and acquisition of universal intellectual assets. They adopt the ideas and practices of general culture. ThatÃ¢â‚¬â„¢s why developing humanistic school culture is a must. Such as (1) multi-faceted cultivation of student personality; (2) developing a social climate of security and fairness; (3) using various types of dialogue with the students in order to reach out to and empower them; (4) developing a community approach and social involvement; (5) developing the studentsÃ¢â‚¬â„¢ intellectual powers by means of general and liberal education; (6) developing teaching techniques in which Ã¢â‚¬Ëœthe tree of knowledgeÃ¢â‚¬â„¢ becomes the studentsÃ¢â‚¬â„¢ and the communityÃ¢â‚¬â„¢s Ã¢â‚¬Ëœtree of lifeÃ¢â‚¬â„¢; (7) ensuring a safe and hospitable physical infrastructure. And also in constructing behavior and affirming behavoir there will be Ã¢â‚¬Å“a golden ruleÃ¢â‚¬Â and Ã¢â‚¬Å“silver rule.Ã¢â‚¬Â It is supported by the concept of 5 eÃ¢â‚¬â„¢s character development. Such as example, experience, environment, education, evaluation.